2001
DOI: 10.1021/ie000939t
|View full text |Cite
|
Sign up to set email alerts
|

Effect Of The Solvent Used During Preparation On The Properties Of Pt/Al2O3 And Pt−Sn/Al2O3 Catalysts

Abstract: The influence of the solvent (water, acetone, and ethanol) used during alumina impregnation on the properties of Pt/Al2O3 and Pt−Sn/Al2O3 catalysts was studied. Catalysts were characterized by H2 chemisorption, TEM, temperature-programmed reduction, ammonia temperature-programmed desorption, UV−vis spectroscopy and cyclohexane dehydrogenation, n-pentane isomerization, and n-octane reforming reactions. It was found that the catalysts prepared in ethanol has the highest metallic dispersion. The results are expla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 44 publications
3
14
0
Order By: Relevance
“…The reduction peak of CoAl 2 O 4 at above 800 8C was not observed. For the Pt/ Al 2 O 3 sample, the TPR result was in good agreement with those reported in literature [25,26] as shown in Fig. 5(b): A peak at about 180 8C attributed to the reduction of Pt and the other observed at higher temperature (320 8C) attributed to the reduction of Pt species interacted with the alumina support.…”
Section: Resultssupporting
confidence: 90%
“…The reduction peak of CoAl 2 O 4 at above 800 8C was not observed. For the Pt/ Al 2 O 3 sample, the TPR result was in good agreement with those reported in literature [25,26] as shown in Fig. 5(b): A peak at about 180 8C attributed to the reduction of Pt and the other observed at higher temperature (320 8C) attributed to the reduction of Pt species interacted with the alumina support.…”
Section: Resultssupporting
confidence: 90%
“…This is probably owing to the high solubility of these metal nitrate salts, that is to say, water can displace ethanol for the preparation of these catalysts in practice. Catalysts such as Al 2 O 3 supported MgO, CeO 2 , and MnO 2 prepared in water have lower DE than those prepared in ethanol, which is probably owing to the poor dispersion of metal oxides (Carvalho et al, 2001). …”
Section: Activity Measurementmentioning
confidence: 99%
“…It is well-known that the superior catalytic performance may be the result of a high dispersion of Pt. , Solar and his co-workers reported the polarity of the solvent, the pH of the impregnating solution, and the isoelectric point of the support determine the extent of the metal precursor and support interaction, which would be responsible for the metal dispersion in the catalyst. Carvalho et al investigated the effect of water, acetone, and ethanol addition on the properties of Pt/Al 2 O 3 and Pt−Sn/Al 2 O 3 catalysts. They found that the catalysts prepared in the solvents have different metallic dispersion, which is attributed to the different boiling point and polarity of the solvents.…”
Section: Introductionmentioning
confidence: 99%